2002
DOI: 10.1023/a:1021851916137
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Since 1995, keratinocytes are grown into cultures and used as allografts for the coverage of deep dermal defects in our burn unit. Donor skin samples are mostly acquired from other burn patients. In addition, special methods of skin preservation allow us the use of skin, which has been taken in redundancy for split thickness skin grafting from nonburned patients.Thirty five patients with deep partial thickness burns in the face were treated since 1996 according to the following concept: Dermabrasion or tangent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…O’Connor et al (1981) reported the use of autologous keratinocyte cultures for the treatment of burns, and over time an increasing number of culture and delivery systems of epithelial grafts were developed, mainly in the burn care field (Madden et al 1986; Herzog et al 1988; Burt et al 1989; Compton et al 1990; De Luca et al 1989; Bolivar-Flores et al 1990; Fratianne et al 1993; Phillips et al 1993; Rue et al 1993; Teepe et al 1993a; Brychta et al 1995, Rivas-Torres et al 1996; Carsin et al 2000; Hiroko et al 2001; Koller et al 2002; Chester et al 2004), but also in dermatology (Roseeuw et al 1989; Teepe et al 1990; De Luca et al 1992; Marcusson et al 1992; Teepe et al 1993b; Lindgren et al 1998; Beele et al 2005), otology (Somers et al 1997a; Somers et al 1997b) and stomatology (Tsai et al 1997). Unfortunately, due to wide patient-to-patient variation and the lack of controlled clinical research, it is currently difficult to tell whether there is a place for cultured epithelial grafts in the treatment of major burns (Wood et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…O’Connor et al (1981) reported the use of autologous keratinocyte cultures for the treatment of burns, and over time an increasing number of culture and delivery systems of epithelial grafts were developed, mainly in the burn care field (Madden et al 1986; Herzog et al 1988; Burt et al 1989; Compton et al 1990; De Luca et al 1989; Bolivar-Flores et al 1990; Fratianne et al 1993; Phillips et al 1993; Rue et al 1993; Teepe et al 1993a; Brychta et al 1995, Rivas-Torres et al 1996; Carsin et al 2000; Hiroko et al 2001; Koller et al 2002; Chester et al 2004), but also in dermatology (Roseeuw et al 1989; Teepe et al 1990; De Luca et al 1992; Marcusson et al 1992; Teepe et al 1993b; Lindgren et al 1998; Beele et al 2005), otology (Somers et al 1997a; Somers et al 1997b) and stomatology (Tsai et al 1997). Unfortunately, due to wide patient-to-patient variation and the lack of controlled clinical research, it is currently difficult to tell whether there is a place for cultured epithelial grafts in the treatment of major burns (Wood et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Allo-ECS are most used in the wound care centre to stimulate the healing of donor sites and treat partial thickness defect wound. [10][11][12] In Korea, cryopreserved allo-ECS product (Kaloderm, Tego Science) was approved and became available as a public health insurance benefit for burn wound treatment. 13,14 However, using of animal-derived feeder layer manufacture allo-ECS can increase risk to deliver animal-borne infection.…”
Section: Introductionmentioning
confidence: 99%